Superior Performance of a Lithium–Sulfur Battery Enabled by a Dimethyl Trisulfide Containing Electrolyte. Issue 6 (26th April 2018) - Chen, Shuru; Wang, Daiwei; Zhao, Yuming; Wang, Donghai
Abstract: The lithium–sulfur (Li‐S) battery offers a high theoretical energy density of ≈2600 Wh kg −1 and low cost, positioning it as a promising candidate for next‐generation battery technology. However, problems including disastrous Li polysulfides dissolution and irreversible Li2 S deposition have severely retarded the development of Li‐S batteries. To solve these issues, a functional dimethyl disulfide (DMDS)‐containing electrolyte was recently reported that promotes an alternate electrochemical reaction pathway for sulfur cathodes by the formation of dimethyl polysulfides and Li organosulfides as intermediates and reduction products, leading to significantly boosted Li‐S cell capacity with improved cycling reversibility and stability. Here, dimethyl trisulfide (DMTS), a primary discharge–charge intermediate in the DMDS‐containing electrolyte, which is also a commercially available reagent, is further investigated as a cosolvent in functional electrolytes for Li‐S batteries. Due to the higher theoretical capacity of DMTS and its better reactivity with Li2 S than DMDS, a 25 vol% DMTS‐containing electrolyte enables Li‐S batteries with even higher cell capacity and improved cycling performance than using previous optimal 50 vol% DMDS‐containing electrolyte. Abstract : Dimethyl trisulfide (DMTS) containing electrolytes enable Li‐S batteries with high initial capacity and enhanced capacity retention, as well as good efficiency in mitigating irreversible deposition of Li2 S. A capacity fading rate as low as 0.11% per cycle is achieved for cathodes with high sulfur content of 70 wt% using an optimal 25 vol% DMTS‐containing electrolyte.